Virus outbreaks and tourism mobility : strategies to counter global health hazards - Kulshreshtha, Sharad Kumar (Tourism security-safety and post conflict destinations., 2021)
The rapid growth and development of global transportation and communication technology systems are some key 21st century drivers, which provide faster, more accessible inter-continental connectivity, continuity, convergence and collaboration to create billions of opportunities for global citizens. Through this tourism has become one of the world's most vital, vibrant, volatile and value-oriented service industries. However, sometimes this mobility may be a great cause of unprecedented pandemics. Recent extensive viral outbreaks such as Zika, Ebola, Swine Flu and the global spanning COVID-19 pandemic have had a momentary disruptive impact of the mobility of tourists and devastated the tourism industry to continue operating. Virus Outbreaks and Tourism Mobility: Strategies to Counter Global Health Hazards uses innovative and cutting-edge research to map out the background and impacts of national, regional and international viral outbreaks. With case studies exploring the strategic responses and management of these crises, with perspectives offered on local economies, tourist destinations or the transport and aviation services, this study focuses on illuminating new viewpoints to help build effective strategic responses to global health hazards.